Using Vfd In Pumping System With Scada - Alhaddar, Alaa; Abuazizeh, Rami; awwad, Osama (جامعة بوليتكنك فلسطين - اتمتة صناعية, 2013)
The use of variable frequency drives (VFD) in pumping variable-duty requirements provides the user with a variety of benefits, including potentially signification energy saving and improved reliability achieved by means of speed reduction, energy saving are primarily realized by running the equipment at high levels of efficiency and optimal operating speeds, matching the generated pump head to exact system requirements without the use of energy consuming control valves. Running pumps at lower operating speeds also positively influences component life and between maintenance intervals. Supervisory control and data acquisition (SCADA) solutions provide a base for more reliable operation of water systems and significant operating and financial benefits, both , which are important to utility management . they provide means for increased productivity , reducing the number of failure events, reduced losses due to damages and minimal losses of potable water. System parameters , which are communicated via Ethernet network present true conditions, and commands sent from SCADA centrals to remote sites that are aimed to
no of pages 80, 26436, اتمتة صناعية 6/2013 , in the store
Keywords: Vfd; Pumping Systems; Scada